2013
DOI: 10.1175/jhm-d-12-0120.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atmospheric Water Vapor on Neutron Count in the Cosmic-Ray Soil Moisture Observing System

Abstract: The cosmic-ray method for measuring soil moisture, used in the Cosmic-Ray Soil Moisture Observing System (COSMOS), relies on the exceptional ability of hydrogen to moderate fast neutrons. Sources of hydrogen near the ground, other than soil moisture, affect the neutron measurement and therefore must be quantified. This study investigates the effect of atmospheric water vapor on the cosmic-ray probe signal and evaluates the fast neutron response in realistic atmospheric conditions using the neutron transport co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
191
3
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(202 citation statements)
references
References 40 publications
7
191
3
1
Order By: Relevance
“…Since neutron counts are mainly related to the amount of hydrogen molecules in an area, raw moderated neutron counts must also be corrected for differences in atmospheric water vapour. Rosolem et al (2013) found the following correction function for atmospheric water vapour:…”
Section: Raw Moderated Neutron Correctionmentioning
confidence: 99%
“…Since neutron counts are mainly related to the amount of hydrogen molecules in an area, raw moderated neutron counts must also be corrected for differences in atmospheric water vapour. Rosolem et al (2013) found the following correction function for atmospheric water vapour:…”
Section: Raw Moderated Neutron Correctionmentioning
confidence: 99%
“…The correction of influencing factors has also received much attention. The analysis and correction of the influences of atmospheric pressure, water vapor, solar activity and aboveground biomass on the neutrons have been studied (Desilets and Zreda, 2001;Moraal et al, 2005;Rosolem et al, 2013;Coopersmith et al, 2014;McJannet et al, 2014;Baatz et al, 2015) and can improve the accuracy of the CRNS. These studies have built the foundation for the application of the CRNS method (Rivera villarreyes et al, 2011;Bogena et al, 2013;Han et al, 2014;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[17] investigated the effect of atmospheric water on low-energy neutrons with Monte-Carlo simulations. Knowing the absolute humidity of air near the surface, h, the correction is then given by:…”
Section: Barometric Effect and Water Vapormentioning
confidence: 99%